ANALISIS STRATEGI BANK SYARIAH DALAM MENINGKATKAN MINAT NASABAH MENGGUNAKAN IB TAHAROH PADA BANK DKI KCPS BEKASI - Siti Nurajijah (2021)
Currently, banks have experienced many developments, one of the problems that often manifests in banks is related to marketing. Therefore, banks are required to determine marketing strategies for iB Taharoh savings products that are accurate in running their business, especially to competitors. The purpose of this study is to explain how the bank's strategy to attract customers' interest using the iB Taharoh savings product at Bank DKI KCPS Bekasi. This research method uses descriptive qualitative method with the type of case study. The results of this study can be concluded that bank DKI KCPS Bekasi in implementing a marketing strategy using the 7P namely product, price, distribution (place) and promotion, people, physical, evidence, prosess. While the promotional mix carried out are sales promotion, public relations and publicity, direct marketing and personal selling. Furthermore, the SWOT analysis of the bank is in quadrant 1. Banks can carry out advanced and developing strategies by utilizing the internal strengths that exist at Bank DKI KCPS Bekasi in obtaining profits from external opportunities, namely by maintaining promotional activities through social media or directly attracting customers' interest so that known by the wider community to achieve increased business growth. Benefits of this research As a review material for consideration of the ability of Islamic banks to compete among other banks. The limitation of this research is that the internal sources only come from active customers who use iB Taharoh products, while the internal sources can come from other experts. Keywords: Islamic Bank, Product Marketing Strategy, Hajj Savings